Reciprocal relationship between the game and training patterns in performance volleyball - Voinea, N.-L.; Rata, G. (Physical Education, Sport and Kinetotherapy Journal, 2019)
There are many types of research in the literature on modelling the game preparation in professional volleyball, but very few have highlighted the relationshipbetween the training pattern and the game pattern, based on the analysis of the performance behaviour of the teams in the official sports competitions. This study aims to highlight the reciprocal relationship between the training pattern and the game pattern in the female performance volleyball for the Stintia Bacauteam depending on the opponent`s level. This research proceeded from the hypothesis according to which the technical-tactical training during the competition period has a positive influence on the game action efficiency markers, in other words, it influences the game pattern. From this interaction we can debate on the reciprocal relationship between the game pattern and the training pattern. The 14 players of the Stintia Bacau women`s volleyball team in the 2017-2018 competitive season took part in the study. As a result of this research, significant differences were recorded in the matches with the level 1 teams for the blocking and taking over game action efficiency indices, and in the matches with the level 2 teams, significant differences in the serve taking over and taking over from the attack as the game action efficiency indices, which confirms the hypothesis of our research.